Case Based Reasoning Diagnosis Hama dan Penyakit Tanaman Nilam - Adawiyah, Rabiah (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2018)
Patchouli is an oil-producing plant asiri known as patchouli oil (oil patchouli oil) which has a high economic value and a bright prospect. Patchouli plants used as cosmetic ingredients, perfumes, antiseptics, soaps, drugs, and insecticides. Patchouli plant is an agribusiness for farmers and entrepreneurs in order to increase the income and welfare (living standard) of the farm community, as well as provider of continuous materials for the patchouli oil industry. In the development and improvement of patchouli plants experience several obstacles such as pests and diseases that resulted in low yields on patchouli plants, especially in the village of Gunung Sari Watubangga District Kolaka. Pests and diseases are one of the causes of the low production of patchouli leaves that should always be anticipated because the development can cause losses for farmers, so it needs to be anticipated early. Handling patchouli plants are attacked by pests and diseases are often hampered because there are still many farmers who are lay in treating patchouli plants that do not know how to handle it. Case Based Reasoning (CBR) is one method that can reason or solve problems based on existing case experiences that are used as solutions to new problems. The system built in this research is the CBR system to make the diagnosis of Nilam Plant disease so that farmers get information about how to properly cultivate patchouli plants. The diagnostic process of inserting a new case compared to the old case then calculated its similarity value using the Nearest neighbord method. The accuracy of the system generated in this research is 80%.